Acid base and metabolic parameters of the umbilical cord blood and cerebral oxygenation immediately after birth - Dusleag, Martin; Urlesberger, Berndt; Schwaberger, Bernhard; Baik-Schneditz, Nariae; Schlatzer, Christoph; Wolfsberger, Christina H.; Pichler, Gerhard (Frontiers in Pediatrics, 2024)
Objective Aim was to investigate whether acid-base and metabolic parameters obtained from arterial umbilical cord blood affect cerebral oxygenation after birth in preterm neonates with respiratory support and in term neonates without respiratory support. Study design This was a post-hoc analysis of secondary outcome parameters of a prospective observational study including preterm neonates with and term neonates without respiratory support. Non-asphyxiated neonates with cerebral oxygenation measured with near-infrared spectroscopy during the first 15 min and with blood gas analyses from arterial umbilical cord blood were included. Arterial oxygen saturation (SpO2) and heart rate (HR) were monitored with pulse oximetry. Potential correlations were investigated between acid-base and metabolic parameters (pH-value, bicarbonate, base-excess, and lactate) and crSO2/cFTOE 5 min after birth. Results Seventy-seven neonates were included: 14 preterm neonates with respiratory support (mean gestational age [GA] 31.4 ± 4.1 weeks; mean birth weight [BW] 1,690 ± 640 g) and 63 term neonates without respiratory support (GA 38.7 ± 0.8 weeks; BW 3,258 ± 443 g). Mean crSO2 5 min after birth was 44.0% ± 24.2% in preterm and 62.2% ± 20.01% in term neonates. Mean cFTOE 5 min after birth was 0.46 ± 0.06 in preterm and 0.27 ± 0.19 in term neonates. In preterm neonates with respiratory support higher lactate was significantly associated with lower crSO2 and SpO2 and tended to be associated with higher cFTOE. In term neonates without respiratory support no significant correlations were found. Conclusion In non-asphyxiated preterm neonates with respiratory support, lactate levels were negatively associated with crSO2 and SpO2, whereas in term neonates without respiratory support no associations were observed.